Screening for sleep apnoea risk in testosterone-treated transgender men - Šnobrová, Bára; Burdová, Kristina; Weiss, Vladimír; Šonka, Karel; Weiss, Petr (Frontiers in Neurology, 2023)
Introduction Obstructive sleep apnoea (OSA) is more prevalent in men. Several studies suggested that higher testosterone levels were associated with a greater risk of OSA. We aimed to determine whether testosterone administration in transgender men would accentuate symptoms of OSA. Methods The study involved 94 adult people undergoing a female-to-male transition with testosterone administration. The participants answered the Berlin Questionnaire (BQ) and a separate question on snoring before starting testosterone treatment and after at least 1 year of being on testosterone treatment. Results A higher proportion of participants at the follow-up answered positively to the first category of BQ devoted to snoring. A lower proportion of participants at follow-up answered positively to the second category of BQ devoted to tiredness. The percentage of subjects with a high risk of sleep apnoea, according to BQ, and of those who answered the question on snoring positively did not change significantly. Conclusion An increased number of transgender men who reported snoring in BQ after testosterone administration indicate a higher risk of OSA development.